PILLAR CAPTION FROM GWALIOR; A STUDY - F.R. Rehman (International Scientific and Current Research Conferences, 2021)
Epigraphy is a significant part of verifiable archaic exploration. It gives substantial realities, yet in addition reveals insight into different parts of antiquated Indian history‒be it political, social, strict or social. In this article an endeavor has been made to examine and break down engravings engraved on two bits of pillars which have been recuperated from a cutting edge asphalt in the Gwalior fortification and now saved in the Gujari Mahal Archaeological Museum of Gwalior. It is in proto-Nāgarī script having 22 refrains in Sanskrit language. Pillars were essential for a sanctuary maṇḍapa. A basic investigation of the pillar engraving arranges it in the last 50% of the 10th century C.E. both based on palaeography just as on inner substance.